Apatinib has anti-tumor effects and induces autophagy in lung cancer cells with high expression of VEGFR-2 - Mingtao Liu; Hui Li (Iranian Journal of Basic Medical Sciences, 2024)
Objective(s): This study investigated the inhibitory effect of apatinib on lung cancer cells with high expression of vascular endothelial growth factor-2 (VEGFR-2) and on inducing cellular autophagy and drug resistance. Materials and Methods: The expression of VEGFR-2 was detected using western blotting and RT-PCR. Cell proliferation was measured using the CCK8 and colony formation assays. The cell apoptosis rate was determined using flow cytometry and tunnel assay. Cellular autophagy was detected by measuring the expression of LC3-II using Western blotting and cellular immunofluorescence. The inhibitory effect of apatinib on lung cancer cells and transplanted tumors was observed after treatment with the autophagy inhibitor chloroquine. Results: Apatinib dose-dependently inhibited the proliferation of H1975 and H446 cells; it induced apoptosis via the PARP and caspase 3 pathways in H1975 and H446 cells and effectively inhibited the growth of transplanted tumors. Apatinib induced autophagy in a dose-dependent manner in H1975 and H446 cells. The inhibitory effect of apatinib on cells and the promotion of apoptosis were significantly enhanced after treatment with chloroquine. Immunohistochemistry showed that combining apatinib with chloroquine could reduce the expression of CD31 and Ki67 and increase the expression of caspase 3. Conclusion: Apatinib inhibits proliferation and induces apoptosis in H1975 and H1446 lung cancer cells with high VEGFR2 expression and autophagy in H1975 and H446 cells.